The Influence of Work Demands on Employee Work Stress at the Office of the Investment and One-Stop Integrated Services (DPMPTSP) South Sulawesi Province - Amelia, Rezki; Maklassa, Maklassa; Andayaningsih, Sri (YUME : Journal of Management, 2025)
Introduction/Main Objectives: This research aims to examine the effect of job demands on work stress of employees at the Investment and One-Stop Service Office (DPMPTSP) of South Sulawesi Province. Background Problems: Employees in government service offices, such as the Investment and One-Stop Service Office (DPMPTSP) of South Sulawesi Province, often face high job demands that may lead to increased work stress. Understanding how these job demands impact employee stress levels is crucial to improving workplace well-being and organizational performance. Novelty: The study focuses on the relationship between job demands and work stress in the specific context of the DPMPTSP of South Sulawesi Province, which may not have been previously studied. Research Methods: The population of this research is all employees of the Investment and One-Stop Service Office (DPMPTSP) of South Sulawesi Province, totaling 50 people. The type of research used is quantitative. The data sources used are primary data, namely information sourced from observations and questionnaires, while secondary data sources are documentation and literature. The data analysis technique used is simple linear regression analysis using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26 application. Finding/Results: The research results show that Job Demands (X) have a positive and significant effect on Work Stress (Y), supported by the calculated t-value of 9.122 > 2.013 t-table and a significance value of 0.000 < 0.05. Conclusion: Job demands significantly and positively influence employee work stress at the DPMPTSP of South Sulawesi Province.(Book Antiqua 11, reguler, spasi 1, spacing before 6 pt, after 6 pt) Kata Kunci: Job Demands, Work Stress of Employees